PENERAPAN METODE GROUP ART THERAPY UNTUK MENURUNKAN KECENDERUNGAN PERILAKU AGRESIF VERBAL PADA ANAK SEKOLAH DASAR - Novisari, Elisabeth Winda (Jurnal Ilmiah Penelitian Psikologi, 2024)
Student of elementary school or the 'middle childhood' period are generally in a development process. The growth process in children can often experience obstacles or experience the emergence of negative behavior that might harm themselves and others. One of the negative behaviors that often occurs is verbally aggressive behavior. The phenomenon that occurred among students at X Elementary School in Semarang, teachers at schools complained about the tendency of verbally aggressive behavior carried out by students in the school environment. The aim of this research is to reduce the tendency for verbal aggressive behavior. Researchers applied the 'Group Art therapy' method to x Elementary School students to reduce the tendency for verbal aggressive behavior. Participants in this study were 6 male students with an age range of 9-10 years. Data collection used observation, interviews and the VAS scale (verbal aggressiveness scale). Based on the results of the validity and reliability test of the Pre Test VAS (verbal aggressiveness scale) with Cronbach's Alpha reliability coefficient of (p>0.05) is 0.259 , while the results of the validity and reliability test of the Post Test VAS (verbal aggressiveness scale) with a Cronbach's Alpha reliability coefficient of (p>0.05) is 0.170, it was concluded that the 20 questionnaire question items were reliable or consistent. This study used a quasi experimental one group pre-test post-test design using the VAS (verbal aggressiveness scale) scale to determine the results before and after giving the Group Art therapy intervention. Data were analyzed using IBM SPSS 22.0 with the non-parametric Wilcoxon Signed Rank test showing that there was a significant difference between verbal aggressive behavior before and after the Group Art therapy intervention (Z = -2.207 and p = 0.027 < 0.05). This research shows that the Group Art therapy method is effective in reducing the tendency for verbal aggressive behavior in the six participants at X Elementary School.